Characterization of Al-Ni intermetallics around 30-60 at% Al for TLPB application - Urrutia, Guillermo Alejandro (2014)
Interest on the Al–Ni equilibrium diagram along the latest years is associated with the attractive properties of its intermetallic phases, such as high thermal stability, high corrosion resistance and high strength to density ratio. The Transient Liquid Phase Bonding (TLPB) is a technological process which can be applied to manufacture new pieces and to perform reparations. Morphology, composition profiles, growth kinetic and hardness as a function of temperature and composition of the Intermetallic Layers (ILs) were analyzed, especially focused on solid–solid interactions during isothermal annealing in reactive diffusion couples Ni/Al (800–1170 °C). The study yields to the following association of the Al–Ni Intermetallic Phases (IPs) to the ILs: L1 (Al3Ni), L2 (Al3Ni2), L3 (Ni-poor AlNi), L4 (Ni-rich AlNi) and L5 (AlNi3). The composition ranges of L3 and L4 are 36–46 and 53–58 at% Al, respectively. Martensitic transformation was found in the half thickness of L4 (L4M and L4S) at 1170 °C. Kinetics show diffusion controlled growth for L2 and L5 and interface reaction control for L4 at 800–1170 °C, while L3 revealed a mixed kinetic behavior: parabolic at 800–1000 °C and linear at 1170 °C. The growth rate constants presented temperature dependence according to the Arrhenius model. Vickers microhardness values decrease with annealing temperature and Ni concentration for ILs, and put in evidence different mechanical properties of L3, L4M and L4S.